The evolution of the GALactose utilization pathway in budding yeasts - Harrison, Marie-Claire; LaBella, Abigail L.; Hittinger, Chris Todd; Rokas, Antonis (Trends in genetics, 2022)
The Leloir galactose utilization or GAL pathway of budding yeasts, including that of the baker’s yeast Saccharomyces cerevisiae and the opportunistic human pathogen Candida albicans, breaks down the sugar galactose for energy and biomass production. The GAL pathway has long served as a model system for understanding how eukaryotic metabolic pathways, including their modes of regulation, evolve. More recently, the physical linkage of the structural genes GAL1, GAL7, and GAL10 in diverse budding yeast genomes has been used as a model for understanding the evolution of gene clustering. In this review, we summarize exciting recent work on three different aspects of this iconic pathway’s evolution: gene cluster organization, GAL gene regulation, and the population genetics of the GAL pathway. The GAL pathway of budding yeasts is a powerful model for inferring the evolutionary principles guiding the evolution of eukaryotic metabolic and genetic pathways.The GAL pathway exhibits substantial variation in its genomic organization across budding yeast species, and a few different mechanisms have driven the evolution of this organization.At least two distinct modes of regulation of the GAL pathway are known in the budding yeast subphylum; there is likely substantial variation between species that use these modes of regulation, and other yet-to-be-discovered modes of regulation likely exist in the subphylum.Population genomic studies have revealed extensive genetic variation, including alternative and highly distinct GAL gene network variants, within budding yeast species, suggesting that yeast populations are subject to varied selection for the utilization of the galactose present in different environments and conditions.